Classificação do nível de atividade física entre pastores protestantes através do IPAQ - Azevedo, Pedro Galoza de (2019)
The life of the pastor happens from a routine of work highly demanding, reaching to reach hourly loads above the common one when compared with other professional activities. We have seen a worrying scenario in the lives of pastors regarding their health, whether physical or emotional. Regular practice of physical activity has proven to effectively prevent and treat many diseases, whether physical or emotional. Therefore, the present study aimed to classify a group of pastors through the IPAQ questionnaire regarding the level of physical activity between active, insufficiently active or sedentary. After applying the questionnaire to a group of 30 shepherds, with a mean age of 36 years, it was observed that 18 are classified as sedentary, 7 as insufficiently active and 5 as active. We conclude with this study that a greater emphasis of the subject is needed between pastors and religious leaders, since the care with the body has direct relation with the spirituality and integral health.